COMPREHENSIVE ASSESSMENT OF AGE-RELATED, GENETIC AND BIOCHEMICAL FACTORS IN THE DEVELOPMENT OF ENDOTHELIAL DYSFUNCTION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Shaienko, Z.O.; Morokhovets, H.Yu.; Akimov, O.Ye. (World of Medicine and Biology, 2025)
The purpose of the study was to assess the role of hereditary factors, antioxidant status, and nitric oxide metabolism in the development of endothelial dysfunction in patients with diabetes mellitus. The study included thirty-three patients. Descriptive evaluation of clinical and biochemical parameters, odds ratio analysis, correlation, and cluster analysis were performed. The results showed that hereditary predisposition increases the risk of endothelial dysfunction by ten times. Strong positive associations were found between hereditary factors, antioxidant activity, and markers of oxidative stress. Cluster analysis identified two subgroups of patients: the first characterized by a high level of oxidative stress with compensatory activation of the antioxidant system, and the second with a more effective antioxidant defense and lower levels of inflammatory markers. The findings emphasize the important role of hereditary factors in the development of endothelial dysfunction in diabetes mellitus and suggest the possibility of distinguishing different phenotypes of the disease course.